A Pilot Feasibility Study of an Intensive Summer Day Camp Intervention for Children with Selective Mutism - Danielle Haggerty; John S. Carlson; Aimee Kotrba (MDPI AG, 2022)
Cost, scheduling, and implementation competency are barriers to accessing traditional evidence-based behavioral interventions for childhood selective mutism (SM). Brief, or intensive, interventions are a disruptive innovation to traditional therapy given the use of fewer sessions during a short-term time period. This study explored the acceptability, integrity, and effectiveness (i.e., single-case replicated AB design) of an intensive summer camp consisting of a 5-day behavioral therapy for 25 children with SM. Caregiver-rated treatment acceptability ratings and family interviews support intensive summer day camp as an acceptable intervention approach for SM. Additionally, results revealed that counselors and parents implemented SM behavioral therapy during camp with impressive integrity (>90%) after receiving training about SM behavioral therapy from an SM expert clinician. Effect size calculations of counselor-rated daily behavior ratings revealed reductions in anxiety during camp for 18 of the 25 campers. Significant caregiver-rated improvements in speaking behaviors were reported for 9 out of 14 campers with data available for analysis at the 3-month follow-up. This pilot feasibility study is the first to investigate intensive summer day camp as a treatment approach for SM and implications for future research are discussed.